Modeling and experimental investigation on the fuel particle heat-up and devolatilization behavior in a fluidized bed. (15th March 2021) - Ke, Xiwei; Engblom, Markus; Cheng, Lu; Chen, Lujian; Cai, Runxia; Hupa, Leena; Lyu, Junfu; Yang, Hairui; Zhang, Man
Graphical abstract: The fuel particle devolatilization model developed in this paper can well reflect the effects of bed temperature and coal particle size on the nitrogen release in a fluidized bed. Highlights: A model is developed aiming at fuel devolatilization behavior in a fluidized bed. A selection principle of 0D and 1D particle models is proposed. The nitrogen content of pyrolytic char is lower than that of parent coal. At a higher degree of devolatilization, the nitrogen content in char decreases. Abstract: The proper understanding and description of fuel devolatilization behavior in a fluidized bed (FB) is important to the FB reactor design and modeling. Aiming at this issue, two different mathematical models, isothermal (0D) particle model and one-dimensional (1D) particle model, have been developed. The particle heat transfer is solved simultaneously using an iterative approach with the existing nitrogen containing chemical percolation devolatilization (CPD-NLG) model. Experiments in a special designed FB reactor were conducted to help validate both the temperature solver and modifications to the fast nitrogen release chemical kinetic parameters. The results show that when the bed temperature is higher or coal size become smaller, the final volatiles yield increases and the nitrogen remaining in char decreases. Under all conditions given in the present study, the final nitrogen content of char is always lower than that of parent coal. The yields of some volatile species are also affected by the coal size and bed temperature. In addition, simulation analysis reveals that the deviation between the results of these two models cannot be ignored if the particle size exceeds a specific value (transition size), namely, the large particle is improper to be described as isothermal during heat-up, while this transition size decreases with the increase of bed temperature. A selection principle of these two models is proposed for balancing the calculation precision and computational time. The particle model developed in this work makes it possible to carry out further FB reactor simulations with the devolatilization process more consistent with laboratory data.